Soluciones administrativas y técnicas para proteger los recursos computacionales de personal interno-insiders (Administrative and technical solutions to protect computational resources from internal-insiders personnel) = (Administrative and technical solutions to protect computational resources from internal-insiders personnel). - Pérez, M.T.; Palomo González, Miguel Ángel (UANL Facultad de Contadura Pblica y Administracin, 2007)
Abstract. Nowadays the organizations know that the computational security in logical, physical, environment security of hardware, software, process of business, data bases, telecommunications, butt in other, are essential not solely for the continuity of the daily operations of the businesses, but also to obtain strategic advantages. If the organization does not worry to place policies of computational security, that does not have control computational security, that does not invest in protection tools, does not update itself in the new problems of internal attacks and that a culture in computational security does not foment, among other aspects, more likely this in a high risk of which some computational resource can be affected by internal personnel and in consequence part or all the Business can let operate. It is necessary to remember that the internal personnel of the areas of information technology or systems intentional business or not intentionally they can damage the computational resources since they have knowledge of the vulnerabilities that have the computational resources. I am made east summary with the purpose of which the people who read it have This paper has the aim to create a TI Resources Security Culture and to present some administrative and technical elements to protect the computational resources of from internalinsiders personnel.